Pentingnya Komunikasi Interpersonal Guru dalam Meningkatkan Kualitas Belajar Siswa - Budi; Neni Nurhasanah; Jelita Ramadhani; Nuria Tri Utami; Uswatun Hasanah (IAI Nasional Laa Roiba Bogor, 2024)
The problem in general is that along with the presence of many educational institutions, both private and state, whether accompanied by the readiness of reliable and qualified teaching staff in accordance with their fields, or it can be said, whether the existing teaching staff (teachers) are in accordance with their competence. This is the question which is a big problem related to the development of the world of education in Indonesia. For example, those at the kindergarten level or also at the level of bringing Play groups. Some factors that cause poor teacher quality include unskilled teachers in teaching, lack of communication with students, teachers do not understand children's characters, teaching methods that are less interesting, then the number of children who are allowed to play, teachers who are impatient in teaching and reduced hours of reading and arithmetic. One form of communication that must be considered carefully for a kindergarten teacher is interpersonal communication.